Prevalência e perfil de resistência de patógenos isolados em uroculturas de gestantes atendidas na rede de saúde pública de um município do Norte de Mato Grosso - Santos, Ludimylla Lins Gondim dos (2022)
Urinary tract infection (UTI) is the invasion and microbial multiplication in the urinary tract. It is one of the most common clinical complications during pregnancy, affecting about 10% of women, and may increase the likelihood of complications such as premature birth, perinatal mortality, and sepsis. In this period, treatment with antimicrobials and prophylaxis are limited due to bacterial resistance and the fact that some drugs are toxic to the embryo/fetus. Considering that early diagnosis of UTIs and appropriate treatment are important to avoid maternal and fetal complications, this study aimed to identify the prevalence and etiology of urinary infections in pregnant women assisted in the public network of a city in the north of Mato Grosso state, as well as to determine the sensitivity profile to antimicrobials of the bacteria isolated. For the research, midstream urine sent to the city's Clinical Analyses Laboratory was analyzed. With the sample collected, urine culture was performed by the technique of sowing on a mat in the CLED agar and MacConkey agar, and after the incubation period the colonies were counted (CFU/mL) and the bacteria were identified. To evaluate the sensitivity profile, the Mueller Hinton agar diffusion technique was performed following EUCAST-BrCAST recommendations. The results indicated that of the 2,357 urine cultures, 201 (8.5%) were processed as positive according to the 1956 Kass criteria. Among the bacteria most associated with UTIs, enterobacteria were predominant, especially Escherichia coli (72.6%), as the main etiologic agent, considering all isolates. Regarding the sensitivity profile, the results showed that 86.8% of the Gram-negative samples were sensitive to nitrofurantoin; the highest resistance rates were found for quinolones (ciprofloxaxin and norfloxacin), both for Gram-negative and Gram-positive bacteria. For the isolated enterobacteria, 2.1% ESBL (Extended-spectrum β-lactamases) strains and 3.7% AmpC (Ampicillin class C β-lactamase) strains were detected phenotypically. It is believed that knowing the profile of antimicrobial resistance is necessary so that the data obtained can contribute to a more appropriate therapy, and thus reduce the rates of bacterial resistance, which is a serious public health problem.